Application of Balloon Blowing Therapy with Pursed Lip Breathing Technique to Improve Oxygen Saturation in Children - Salsabella Septa Widyowati; Irdawati Irdawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Respiratory issues are frequent in children and can lead to reduced oxygen levels. One non-medical approach that may be beneficial is Pursed Lip Breathing (PLB), which can enhance the exchange of oxygen and lower the respiratory rate. This research aimed to assess the effectiveness of balloon blowing therapy utilizing the PLB technique to improve oxygen saturation in children. A case study design with a nursing perspective was used, involving 11 children aged 4 to 8 years who were experiencing respiratory issues. The participants were selected using purposive sampling, focusing on children who met specific inclusion criteria. Data collection included measurements of respiratory rate (RR) and oxygen saturation (SpO₂) before and after the intervention, taken using a pulse oximeter. Paired t-tests and Pearson correlation were used for statistical analysis. The average respiratory rate reduced from 40.27 to 30.73 breaths per minute, while oxygen saturation increased from a range of 91–93% to 95–98%. The correlation coefficient between the pre- and post-intervention values was r = 0.823 (p = 0.002), indicating a strong and statistically significant relationship. These findings suggest that the intervention effectively decreased respiratory effort and enhanced oxygenation in children.Balloon blowing therapy with the PLB technique proves to be an effective, straightforward, and non-invasive method for improving respiratory function in children.